Localized amyloidosis of the epididymis: a previously unreported phenomenon - Lucio Díaz-Flores; Ricardo Gutiérrez; Ma. del Pino García; Manuel Jose Gayoso; Jose Luis Carrasco; Lucio Díaz-Flores; Hugo Álvarez-Argüelles (BMC, 2017)
Abstract Background Localized amyloidosis has not been documented in the epididymis; we report this phenomenon for the first time. Case presentation The first aim of this work is to report three cases of localized epididymal amyloidosis. Two cases were clinically detected as epididymal nodules, and a third after reviewing 120 epididymides obtained with neighbouring pathological processes. Amyloid deposits showed Congo red positivity, with yellow-green birefringence, and immunohistochemical expression for light chains kappa and lambda, transthyretin, amyloid P and cytokeratin AE1 AE3. No immunoreactivity for amyloid A was seen. Amyloid deposit location was intraluminal, with partial or total loss of the epididymal epithelium and subsequent passage to the interstitium, forming large masses. No amyloid deposits were observed around blood vessels. A secondary objective was to explore in normal epididymis the amyloid tested in epididymal amyloidosis. In normal epididymides, expression of amyloid P and transthyretin was detected in the apical surface of epithelial cells. Amyloid P also showed strong expression in spermatozoa. Conclusion We contribute the existence of localized epididymal amyloidosis, which presents a distinctive, initial intratubular location, where there is a unique proteome and where functional amyloids act during sperm maturation.